Transition Metal Dichalcogenides (WS2 and MoS2) Saturable Absorbers for Mode-Locked Erbium-Doped Fiber Lasers - Kadir, N.A.A.; Ismail, Ezzatul Irradah; Latiff, Anas Abdul; Ahmad, Harith; Arof, Hamzah; Harun, Sulaiman Wadi (IOP Publishing, 2017)
We demonstrate an ultrafast fiber laser based on transition metal dichalcogenide materials which are tungsten disulfide (WS2) and molybdenum disulfide (MoS2) as saturable absorber (SA). These materials are fabricated via a simple drop-casting method. By employing WS2, we obtain a stable harmonic mode-locking at the threshold pump power of 184mW, and the generated soliton pulse has 3.48MHz of repetition rate. At the maximum pump power of 250mW, we also obtain a small value of pulse duration, 2.43 ps with signal-to-noise ratio (SNR) of 57 dB. For MoS2 SA, the pulse is generated at 105mW pump power with repetition rate of 1.16 MHz. However, the pulse duration cannot be detected by the autocorrelator device as the pulse duration recorded is 468 ns, with the SNR value of 35 dB.